FACTORS AFFECTING THE SELECTION OF INVENTORY VALUATION METHODS IN INDUSTRIAL COMPANIES IN INDONESIA STOCK EXCHANGE - Rioni, Yunita Sari (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2019)
The purpose of this study is to prove and analyze the factors that influence the choice of inventory valuation methods in industrial companies on the Indonesia Stock Exchange. In this study, an associative quantitative research approach was used, namely research aimed at examining the effect or relationship between two or more variables. The data analysis technique used logistic regression analysis method. Logistic regression is an analytical tool used to measure the influence of the independent variable on the dependent variable in the form of a dummy variable. The results of data analysis and discussion prove that company size (SIZE) has an effect on the selection of inventory valuation methods for industrial companies on the IDX for the 2015-2017 period. Inventory intensity affects the selection of inventory valuation methods for industrial companies on the IDX for the 2015-2017 period. Simultaneously company size (SIZE), and Inventory Intensity affect the selection of inventory valuation methods for industrial companies on the IDX for the 2015-2017 period. The greater the size of the company, the more access it can be for managers to establish a constant (unchanging) inventory valuation method. Companies that are larger in size are thought to have a greater tendency to choose the correct method. Based on the political cost hypothesis in positive accounting theory, it is stated that large companies tend to manage their inventory well. Changes in the inventory valuation method from the average method to FIFO will cause the company's profits to be higher and it is expected that the company's shares can be sold at a price that is favorable to the company. The results of this study indicate that the net profit margin has an effect on the choice of inventory valuation method because the companies used in this study are companies that earn profits.